2019
DOI: 10.3390/ijerph16122203
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Willingness of Patients with Type 2 Diabetes Mellitus to Receive the Seasonal Influenza Vaccine in Southeast China

Abstract: Willingness of patients with Type 2 diabetes mellitus (T2DM) to receive the seasonal influenza vaccine is low in China. A cross-sectional study on a representative sample of T2DM patients was conducted in Ningbo, a city in southeast China, to assess T2DM patients’ willingness to be vaccinated against influenza and identify the influence factors of this willingness. Data regarding the participant’s history of influenza, the knowledge, willingness and uptake of the influenza vaccine, demographic characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 29 publications
(31 reference statements)
2
14
2
Order By: Relevance
“…Sixty-one studies reported perceived barriers to receiving an influenza vaccination in the total population ( Table 4 ) [ 16 , 17 , 19 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixty-one studies reported perceived barriers to receiving an influenza vaccination in the total population ( Table 4 ) [ 16 , 17 , 19 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , …”
Section: Resultsmentioning
confidence: 99%
“…Barrier types were further assessed to determine the key factors (determined by agreement rate) across the general and unvaccinated population for not receiving an influenza vaccine. The top-five barriers to influenza vaccination, as reported by the total population compared to the unvaccinated population, are illustrated in Figure 3 [ 16 , 17 , 19 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 40 , 41 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study in China indicated merely 19.6% of patients with type 2 diabetes mellitus were willing to get vaccinated during the 2016/2017 influenza season. 32 Another research suggested that 20% of Canadian individuals aged over 50 years who had planned to skip the influenza shot had changed their minds in light of COVID-19 in the 2020/2021 season. 33 These suggested that the COVID-19 pandemic had an impact on raising public awareness of health issues and disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…The willingness of patients with type 2 diabetes mellitus in Southeast China to receive influenza vaccine was associated with their opinion that persons with diabetes were susceptible to the infection, knowledge that the vaccine is available and the fact that they were vaccinated against influenza in the past seasons (43).…”
Section: Seasonal Influenza Immunization and People With Diabetesmentioning
confidence: 99%